Web-based Population Administration Service Information System In Kutabumi Tangerang Village - Saryani, Saryani; Ningsih, Rohmawati; Sari, Puspita Indah (Pandawan Sejahtera Indonesia, 2021)
The Kutabumi Kelurahan office is an office that carries out several activities to carry out government affairs, such as empowerment and service to the community. Population administration services are important in a government agency in the Kutabumi District Office. Problems that occur include the making of a request letter that is still semi-computerized using Microsoft Word and Microsoft Excel. So that the impact on services that are less effective and maximal to the needs of its residents. The system certainly has many weaknesses including the accumulation of paper and vulnerable to data loss because the data is not stored in the database. To improve the existing quality services at the Kutabumi Village Office, an administrative service system is needed so that administrative services are more effective and efficient. The analytical method used by researchers is the PIECES method (Performance, Informance, Economy, Control, Efficiency, Service). With this administration system, it can facilitate the process of requesting requirements regarding population administration and facilitate service staff in the process of population administration report activities.